Sistema de vigilancia mediante cámaras ip en las oficinas de la capitanía del puerto de la ciudad de Manta - Zambrano Zambrano, Gema Victoria (2014)
This thesis aimed to implement a surveillance system based on IP cameras at the Port Authority of Manta’s city, which obtained effective capture images and videos using a face detection software. This system allows a database of each people who enter the institution, achieving monitor everything that takes place in the offices where the cameras are located above. To carry out the software and implementation of the monitoring system was conducted using the methodology of Life Cycle V and ITIL, which were developed through stages himself as the technical measures necessary for this scope. However for the collection of information is worked based on the inductive-deductive scientific method, which allowed the generation of the provisions and an analysis of the issues raised based on the requirements of the institution, being necessary to develop a software face detection codes used by Java and framework as opencv and javacv, which was designed to be monitored by security cameras Trendnet TV- IP551W. The system is a useful and easy to handle application that allows remote access to the stored images and to control and identify people entering and detect if any of these is performing any activity that threatens the proper functioning of the processes that take place within their offices.